Effects of music combined with sports games on enhancing psychological well-being among adolescents in lanzhou gansu province China during covid-19 pandemic - Jiarun, Wu (2024)
Since December 2019, global COVID-19 impact has caused widespread psychological distress. While sports games and music therapy alleviate adolescent stress, their combined effectiveness is underexplored. In GanSu, China, this study explores relationships between stress, anxiety, fear of COVID-19, athletic mental energy (AME), mental toughness (MT), physical literacy (PL), positive achievement emotion (AE-P), negative achievement emotion (AE-N), and the impact of music combined with sports games on secondary school-aged adolescents. The specific objectives are divided based on study’s phase 1 and 2. Phase 1, Objective 1 – 7: This phase aimed to assess the reliability and validity of Chinese versions of key psychological scales related to epidemics. Through multistage cluster sampling, 729 participants were included. CFA validated the questionnaires, and test-retest reliability verification involved 72 participants after a 14-day interval. Concurrent measures like Generalized Anxiety Disorder (GAD-7) and physiological indicators (cortisol, HR, SpO2) were collected. Results indicated good model fit. Phase 1, Objective 8: This phase aimed to assess stress-related factors among 797 Chinese college students in GanSu province. Descriptive statistics, independent sample t - test, regression analysis, SEM, and Bootstrap mediation effect were employed. Results indicated that PL positively influenced AE-P, MT, and AME, while negatively affecting AE-N and COVID-19-induced negative mental state (NMSC). Phase 2, Objective 9 & 10: This phase aimed to assess the impact of combining music with sports games on stress-related factors among 200 secondary school-aged adolescents in GanSu province, China. Participants from Phase 1 (n = 200) enrolled in the intervention study, randomly assigned into three intervention groups and one control group using block randomisation. Results: In the SAVE-6, a significant main effect of time on anxiety and interaction effect with groups were found (p < 0.01). However, the main effect of the group was not significant (p > 0.05). Further simple effect analysis revealed significant individual effects for groups in the post-test (p < 0.05). Similarly, for FCV-19, AEAL-Positive, AEAL-Negitive, PPLA-Q, AMES, MTQ-48, pulse oxygen saturation, heart rate, and serum cortisol, significant main effects of time and interaction effects with groups were observed (p < 0.05 or p < 0.001). In most cases, the main effect of the group was not significant (p > 0.05), while further simple effect analysis demonstrated significant individual effects for groups in the post-test (p < 0.05). The main conclusions drawn from the above research were as follows: (1) SAVE-6, FCV-19, AMES, MTQ-48, PPLA-Q and AEAL demonstrated good reliability and validity and were recommended for use among Chinese university students. (2) Relationships identified: 1) PL had a direct negative impact on NMSC. 2) PL positively predicted AME, MT and AE-P. 3) AE-P negatively affected NMSC. 4) AME, MT and AE-N, directly influenced NMSC. 5) AME, MT, AE-P and AE-N, mediated PL's impact on NMSC. These findings offer insights for targeted interventions to enhance students' overall well-being. (3) An 8-week music combine sports games intervention ‘s effect was better than other intervention’s effect. It might have a positive effect on NMSC, AME, MT, PL, AE-P and AE-N. Therefore, we recommended using this intervention approach in adolescents setting.